2011
DOI: 10.1001/jama.2010.1919
|View full text |Cite
|
Sign up to set email alerts
|

Association of a MicroRNA/TP53 Feedback Circuitry With Pathogenesis and Outcome of B-Cell Chronic Lymphocytic Leukemia

Abstract: HRONIC LYMPHOCYTIC LEUkemia (CLL) is the most common leukemia among a d u l t s i n t h e W e s t e r n world, with an annual incidence in the United States of approximately 10 000 new cases. 1 The clinical stag-ing systems devised by Rai et al 2 and Binet et al 3 are useful for assessing the extent of CLL in a patient, but they fail to differentiate between the indolent and aggressive forms of CLL. Most typically these forms are characterized by low and high levels of zeta-chain (TCR)-associated See also p 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
254
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(268 citation statements)
references
References 31 publications
7
254
0
6
Order By: Relevance
“…The results of these experiments suggest that tsRNAs could be key effectors in pathways regulated by these oncogenes and that these molecules could have important roles in the cell transformation process and in cancer development/progression. Additionally, the oncogenedriven dysregulation of tsRNA could be involved in feedback loops, as previously shown for miRNAs (34). Indeed, when profiling the gene-expression patterns of ts-46 and ts-101 KO cells, we found that pathways such as PTEN and ceramide signaling are inhibited.…”
Section: Discussionsupporting
confidence: 66%
“…The results of these experiments suggest that tsRNAs could be key effectors in pathways regulated by these oncogenes and that these molecules could have important roles in the cell transformation process and in cancer development/progression. Additionally, the oncogenedriven dysregulation of tsRNA could be involved in feedback loops, as previously shown for miRNAs (34). Indeed, when profiling the gene-expression patterns of ts-46 and ts-101 KO cells, we found that pathways such as PTEN and ceramide signaling are inhibited.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, doxorubicin-mediated TP53 activation in MEG-01 cells increased the expression of miR-16, an effect that was abolished when TP53 was silenced by an anti-TP53 oligonucleotide. 30 We also identified a binding site for both miR-15 and miR-16 inside the 3 0 UTR of TP53. A luciferase reporter assay showed that both miR-15 and miR-16 directly target the identified TP53-binding site and significantly reduced the luciferase reporter activity compared with a scrambled oligonucleotide-negative control.…”
Section: Mir-15/16 At 13q14 Gene Discoverymentioning
confidence: 78%
“…A luciferase reporter assay showed that TP53 significantly increased the luciferase reporter activity of all the binding site containing vectors. 30 In MEG-01 cells, TP53 transactivation of the miR-15/16 cluster was also confirmed by real-time reverse transcription-PCR. Similarly, doxorubicin-mediated TP53 activation in MEG-01 cells increased the expression of miR-16, an effect that was abolished when TP53 was silenced by an anti-TP53 oligonucleotide.…”
Section: Mir-15/16 At 13q14 Gene Discoverymentioning
confidence: 78%
See 2 more Smart Citations